ÃÂªÃÂ¯ÃÂ±ÃÅ ÃÂ³ Ãâ¦ÃÂÃÂ±ÃÂ¯ÃÂ§ÃÂª ÃÂ§ÃâÃâÃÂºÃÂ© ÃÂ§ÃâÃÂ¹ÃÂ±ÃÂ¨ÃÅ ÃÂ© ÃË ÃÂ§ÃÂ®ÃÂªÃÂ¨ÃÂ§ÃÂ±ÃÂ§ÃÂªÃâ¡ÃÂ§ ÃâÃâ¦ÃÂ±ÃÂÃâÃÂ© ÃÂ§ÃâÃâ¦ÃÂªÃËÃÂ³ÃÂ·ÃÂ© - Zukhaira, - (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Teaching vocabulary (mufrodat) is the basic foundation that must be mastered in the learning of foreign languages including Arabic. Learners can not communicate with Arabic without having sufficient vocabulary to communicate well. The goal of teaching vocabulary (mufrodat) Arabic for intermediate level is that the student has the repertory 700-1500 vocabulary to be able to communicate orally and in writing, and be able to use appropriate vocabulary in the correct sentence. Methods and techniques of teaching, the media used, and evaluation in the teaching of vocabulary should be adjusted to the development and needs of learners. (Pengajaran kosakata (mufrodat) merupakan landasan dasar yang harus dikuasai dalam pembelajaran bahasa asing termasuk bahasa Arab. Pembelajar tidak dapat berkomunikasi dengan bahasa Arab tanpa memiliki kosakata yang cukup untuk berkomunikasi dengan baik. Tujuan dari pengajaran kosakata (mufrodat) bahasa Arab untuk tingkat menengah adalah agar pelajar memiliki perbendaharaan kosakata 700-1500 untuk dapat berkomunikasi secara lisan dan tulisan, dan mampu menggunakan kosakata yang sesuai dalam kalimat yang benar. Metode dan teknik pengajaran, media yang digunakan, dan evaluasi yang dilakukan dalam pengajaran kosakata haruslah disesuaikan dengan perkembangan dan kebutuhan pembelajar. ) Key words: vocabulary, Arabic, intermediate level kosakata, bahasa Arab, tingkat menengah Teaching vocabulary (mufrodat) is the basic foundation that must be mastered in the learning of foreign languages including Arabic. Learners can not communicate with Arabic without having sufficient vocabulary to communicate well. The goal of teaching vocabulary (mufrodat) Arabic for intermediate level is that the student has the repertory 700-1500 vocabulary to be able to communicate orally and in writing, and be able to use appropriate vocabulary in the correct sentence. Methods and techniques of teaching, the media used, and evaluation in the teaching of vocabulary should be adjusted to the development and needs of learners. (Pengajaran kosakata (mufrodat) merupakan landasan dasar yang harus dikuasai dalam pembelajaran bahasa asing termasuk bahasa Arab. Pembelajar tidak dapat berkomunikasi dengan bahasa Arab tanpa memiliki kosakata yang cukup untuk berkomunikasi dengan baik. Tujuan dari pengajaran kosakata (mufrodat) bahasa Arab untuk tingkat menengah adalah agar pelajar memiliki perbendaharaan kosakata 700-1500 untuk dapat berkomunikasi secara lisan dan tulisan, dan mampu menggunakan kosakata yang sesuai dalam kalimat yang benar. Metode dan teknik pengajaran, media yang digunakan, dan evaluasi yang dilakukan dalam pengajaran kosakata haruslah disesuaikan dengan perkembangan dan kebutuhan pembelajar. ) Key words: vocabulary, Arabic, intermediate level kosakata, bahasa Arab, tingkat menengah